2005
DOI: 10.7326/0003-4819-143-12-200512200-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing the Intensity of Implementing Pneumonia Guidelines

Abstract: Both moderate-intensity and high-intensity guideline implementation strategies safely increased the proportion of low-risk patients with pneumonia who were treated as outpatients. The high-intensity strategy was most effective for increasing the performance of the recommended processes of care for outpatients and inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 31 publications
7
143
0
4
Order By: Relevance
“…PCT stewardship markedly reduced antibiotic exposure in patients with CAP, mainly by individually reducing the median duration of antibiotic courses from 12 to 5 days. In the PCT group, antibiotic courses were markedly shorter, as suggested by current guidelines [72,76]. Conversely, CAP is associated with adverse outcome, especially in bacteraemic patients, and thus longer antibiotic courses are recommended [77][78][79].…”
Section: Pct For Antibiotic Stewardship Of Respiratory Tract Infectionsmentioning
confidence: 99%
“…PCT stewardship markedly reduced antibiotic exposure in patients with CAP, mainly by individually reducing the median duration of antibiotic courses from 12 to 5 days. In the PCT group, antibiotic courses were markedly shorter, as suggested by current guidelines [72,76]. Conversely, CAP is associated with adverse outcome, especially in bacteraemic patients, and thus longer antibiotic courses are recommended [77][78][79].…”
Section: Pct For Antibiotic Stewardship Of Respiratory Tract Infectionsmentioning
confidence: 99%
“…Thus both scoring systems use patient's age as an important parameter. However, these systems are not effective to assess patients with a high mortality risk as much as it is for measuring patients with a low mortality risk 8,9 . In addition to PSI and CURB-65, biological markers have been developed to predict the severity of pneumonia in patients during the early infection.…”
Section: Original Articlementioning
confidence: 99%
“…We found no association between guideline- accordance with the guidelines that had been implemented. (13) In a study that constituted an arm of the abovementioned study, Aujesky et al found that 78.7% of the hospitalizations among the 1,306 patients under study were in accordance with the pneumonia severity index after a high intensity of implementing guidelines. (14,15) Our finding might be due to the fact that the HC/ UFMG is a university hospital, reflecting greater knowledge of the guidelines for CAP.…”
Section: Discussionmentioning
confidence: 99%